Particle sizing and flow measurements in an atomising mist jet nozzle: a Shadowgraphy approach - PERSOONS, TIM; MURRAY, DARINA BRIDGET (My University, 2010)
Particle sizing and velocity measurements are undertaken in an atomizing water mist jet impinging onto a heated copper plate. This study forms part of an investigation into the heat transfer and flow field obtained from the mist jet. The droplet sizes obtained are compared to manufacturer?s data. This analysis is performed for the near field and mid field. Ultimately, the effects of particle sizes and velocities will aid the understanding of the heat transfer mechanisms involved.
PUBLISHED
Keywords: Medical engineering; shadowgraphy; mist jet